Climate and human exploitation have regulated Atlantic salmon populations in the River Spey, Scotland, over the last 2000 years. (August 2022) - Sear, David; Langdon, Pete; Leng, Melanie; Edwards, Mary; Heaton, Tim; Langdon, Catherine; Leyland, Julian
Historical salmon catch records suggest that climatic variability, and more recently human exploitation, control patterns of abundance in Atlantic salmon populations. We present the first long-term (2000-year) reconstruction of Atlantic Salmon population variations based on a Marine Derived Nutrient (MDN) lake sediment record. Our record is constructed from nitrogen isotopes (δ 15 N) measured from a lake sediment core, which we compare with an escapement index (EI) derived from historic net catch data on major Scottish salmon rivers. We used an isotope mixing model to demonstrate that the N isotope values are likely enriched with MDN and demonstrate that Loch Insh sediments are enriched compared with a control site (Loch Vaa) that has never had exposure to salmon. We demonstrate that current adult spawner returns are around half that of historic values prior to major human exploitation. Before the onset of widespread human exploitation and habitat degradation, large fluctuations in salmon abundance are attributed to variations in North Atlantic sea surface temperature. While our data support published reconstructions of declining Atlantic salmon stocks in Northwest European rivers over the last 1000 years, rather than point to a solely human cause, the human impact appears to be overprinted on larger-scale changes in marine habitat occurring at the transition from the warmer Medieval Climatic Anomaly (MCA) to the cooler Little Ice Age (LIA).